Influence Leadership Management for the Management of Madrasah Facilities and Infrastructure at MTs Negeri 2 Deli Serdang - Muhammad Alfi Syahrin; Khairuddin Lubis; Halimahtunsakdiah Halimahtunsakdiah (Edumaspul: Jurnal Pendidikan, 2023)
Seeing the importance of facilities and infrastructure in supporting education, MTs Negeri 2 Deli Serdang is a State Madrasah with Accreditation A where in principle the educational facilities and infrastructure have met existing needs. However, by only meeting existing needs, it cannot run well if the management is not correct. the purpose of this study was to find out what kind of influence Leadership Management has on the management of madrasah facilities and infrastructure at MTs Negeri 2 Deli Serdang. The type of research that the author used in research at MTs Negeri 2 Deli Serdang was quantitative descriptive research. To obtain complete data, the authors use data collection tools in the form of observation, data analysis, and documentation. Based on the results of the study it is understood that the Effect of Leadership Management on the Management of Madrasah facilities and infrastructure at MTs Negeri 2 Deli Serdang which includes: First the planning activities for facilities and infrastructure are always carried out starting from needs analysis, determining the place of goods and selecting goods needed, Second procurement activities have been running starting from dropping the government and procuring schools by buying and determining funds as needed but there are still procurement activities that have not been running. Third, the use of facilities and infrastructure is always carried out to support learning. Fourth, maintenance of facilities and infrastructure is carried out regularly by involving madrasa residents The five inventories are always carried out as evidence of procurement of goods. The six write-off activities have already been carried out. From the results of the research above, it can be concluded that the Influence of Leadership Management on the Management of Madrasah Facilities and Infrastructure at MTs Negeri 2 Deli Serdang has been fulfilled by means of: planning needs, procurement , use , maintenance, inventory, write-off and accountability.